Digital Transformation in the Concept of Internal Banking Risk Management - D. V. Pasinitsky (Цифровая трансформация)
The article is devoted to a targeted analysis of promising displacements in the guiding ideas of managing internal banking risks. Based on the study, the author proposes to intensify the introduction of digital technologies in banking practice based on: artificial intelligence, machine learning, data mining.